THE PRACTICE OF TALAQQI RUKBAN AMONG FISHERMEN IN TANJUNG BALAI FROM THE PERSPECTIVE OF WAHBAH AZ-ZUHAILI - Manurung, Sefty Adelia; Ramadhan, Muhammad (Program Pascasarjana UIN Sumatera Utara, 2026)
This research examines the practice of talaqqi ruqban in buying and selling transactions of fishermen's catches in Tanjung Balai, North Sumatra, using the muamalah jurisprudence perspective of Wahbah Az-Zuhaili. This practice occurs when wholesalers buy fishermen's catch directly in the middle of the sea before fishermen enter the market, at prices that tend to be lower than market prices. This research aims to analyze the characteristics of this practice empirically and assess its conformity with the principles of justice, transparency and protection of the weak in Islamic law. The method used is empirical legal research with a qualitative approach through in-depth interviews, field observations, and studies of classical and contemporary jurisprudence literature. The research results show that although fishermen subjectively feel helped and are willing to carry out transactions, this practice has the potential to weaken fishermen's bargaining position and cause market distortions due to information asymmetry and economic dependence on contractors.